A stronger reformulation of Webb's conjecture in terms of finite topological spaces - Piterman, Kevin (2019)
We investigate a stronger formulation of Webb's conjecture on the contractibility of the orbit space of the p-subgroup complexes in terms of finite topological spaces. The original conjecture, which was first proved by Symonds and, more recently, by Bux, Libman and Linckelmann, can be restated in terms of the topology of certain finite spaces. We propose a stronger conjecture, and prove various particular cases by combining fusion theory of finite groups and homotopy theory of finite spaces.